The validity and reliability of a novel indoor player tracking system for use within wheelchair court sports - Rhodes, James M.; Mason, Barry S.; Perrat, Bertrand; Smith, Martin; Goosey-Tolfrey, Victoria L. (Routledge, 2014)
The aim of the current study was to investigate the validity and reliability of a radio- frequency based system for accurately tracking athlete movement within the wheelchair court sports. Four wheelchair specific tests were devised to assess the system during i) static measurements ii) incremental fixed speeds iii) peak speeds, and iv) multi-directional movements. During each test, three sampling frequencies (4, 8 & 16 Hz) were compared to a criterion method for distance, mean and peak speeds. Absolute static error remained between 0.19-0.32 m across the session. Distance values (test ii) showed greatest relative error in 4 Hz tags (1.3%), with significantly lower errors seen in higher frequency tags (< 1.0%). Relative peak speed errors of < 2.0% (test iii) were revealed across all sampling frequencies in relation to the criterion (4.00 ± 0.09 m·sˉ¹). Results showed 8 and 16 Hz sampling frequencies displayed the closest to criterion values, whilst intra-tag reliability never exceeded 2.0% coefficient of variation (% CV) during peak speed detection. Minimal relative distance errors (< 0.2%) were also seen across sampling frequencies (test iv). To conclude, the indoor tracking system is deemed an acceptable tool for tracking wheelchair court match-play using a tag frequency of 8 or 16 Hz.